Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti dengan Model PBL (Problem Based Learning) Berbantuan Media Power Point Fase E SMK Negeri 6 Bandung - Fransiska Wayan Meila Candraningsih; Y.L. Sukestiyarno; Martina Murlani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education and Character Education using the Problem Based Learning (PBL) model assisted by PowerPoint media at SMK Negeri 6 Bandung, Phase E. This research is classified as Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of several stages: planning, implementation, and evaluation. The first cycle covers the topic